THE INFLUENCE OF THE MEDIA ON THE FORMATION OF SOCIAL NORMS IN ADOLESCENTS - Akhmatova Madina Akrom kizi (Web of Journals Publishing, 2025)
The article reveals the role of mass media in the development of legal awareness and legal culture of adolescents, the content and features of positive and destructive information impact on the legal awareness of adolescents, and presents the main directions for overcoming counteraction to destructive information impact.
Keywords: Information impact, legal consciousness, information and legal culture, media education.